A numerical method of solving a heat - mass transfer problem in porous media with moving boundary - Hai, Duong Ngoc (Vietnam Journal of Mechanics, 1989)
In the framework of the methods, of multiphase media mechanics the thermo it hydrodynamic process induce by interaction between high-frequency electromagnet ic field and porous medium (first component) containing the second component, which can melt at the temperature Tm and the fluid phase of the latter can move to pressure gradient, is considered. This problem is solved by the combination of native method with sweep method. The effectiveness of iterative coefficient is ermined.